The System of Civil Rites in the Anti-Religious Policy of the Soviet Government of the 1920s in the North-West of the RSFSR - Tabachnik, Ksenia K. (Вестник Свято-Филаретовского института)
The article is dedicated to the anti-religious program of “red rites”: “The Octobering”, “Red Weddings” and “Civil Funerals” in the 1920s. The ideological goal of the ritual-making campaign of the 1920s is revealed. Among the tasks of developing non-religious “red rites”, the self-identification of the political elite of the Soviet society and advanced Komsomol youth is noted; elimination of “religious remnants” among the population; consolidation of Soviet society on Marxist-Leninist principles and mobilization of the population to solve urgent political and economic problems. Attention is paid to the specifics of the “red rite” as a special socio-cultural and social phenomenon of the pre-war Soviet society. Among the most important signs of the “red rites” of the family and household cycle, the author highlights their politicized nature, focus on expressing public feeling and the fact of collective creativity in the development of Soviet rituals on the ground. Based on materials from archival documents, pamphlets by Soviet propagandists and major figures of the Bolshevik Party, periodical sources from the funds of the State Museum of the History of Religion, photographic documents, the author attempts to prove the actual borrowing of Christian attributes and their transformation in a revolutionary way. The issue is raised on the reflection of society’s attitude to the “red rite” in fiction and the journalistic press. In addition, the author traces the results of the ritual-making campaign of the 1920s and the reasons for the refusal of the Soviet government from the policy of developing the “red rites” as one of the main means of fighting religion among the urban and rural population.